Today's Nutrition and Tomorrow's Public Health: Challenges and Opportunities - Dominique J. Dubois (Frontiers Research Topics, 2016)
At the dawn of the third millennium, we are confronted with a disturbing phenomenon: although global life expectancy still increases, this is not the case for healthy life expectancy! The explanation of this seemingly contradiction is mainly due to the rising prevalence of the new pandemia of chronic non-communicable diseases (NCDs). Even in low and middle income countries, the improvement in healthcare status and life expectancy is paralled by the increase of NCDs, as in all countries worldwide. Since the United Nations General Assembly held in New York in 2011, many publications have emphasized the close link between NCDs and nutrition. The NCDs epidemic forces us to reconsider the public health perspectives. Many governments, non-governmental organizations and other institutions are actively involved in educational nutrition programs and campaigns; however their efforts seldom obtain the results hoped for. It is extremely difficult to induce changes in lifestyle and behavior that have built up over a long period of time. However, it becomes urgent to adapt to our changing life-environment where traditional wisdom and intuitive choices are giving way to individual thinking and search for (often uncontrolled) information. This engenders a number of unprecedented challenges and it calls for a re-appraisal of the existing paradigms to achieve an adequate management of the upstream determinants of health instead of a (pre)dominant medical and hospital-centric approach. In the era of personalized healthcare, it is time to empower policy makers, professionals and citizens for achieving an evidence-based change in the health-disease interface and decision-making process for public health interventions. The scientific and professional society Health Technology Assessment International (HTAi) has recognized nutrition as a health technology by creating a Interest Group (IG) dedicated to research on methodologies and assessments of nutrition-related public health, while taking into account contextual factors (ethical, legal, social, organizational, economic, ...) in order to generate meaningful outcomes for establishing evidence-based health policies. This Research Topic aims to elaborate on some of the potential hurdles which have to be overcome for the sake of sustainable healthcare provisions anywhere in the world, such as shortcomings in methodological approaches, regulatory frameworks, gaps between evidence, its hierarchy and final recommendations for public health management.